2006
DOI: 10.1158/0008-5472.can-05-2755
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Bladder Tumor Growth by 1,1-Bis(3′-Indolyl)-1-(p-Substitutedphenyl)Methanes: A New Class of Peroxisome Proliferator-Activated Receptor γ Agonists

Abstract: 1,1-Bis(3V -indolyl)-1-(p-substitutedphenyl)methanes containing p-trifluoromethyl (DIM-C-pPhCF 3 ), p-t-butyl (DIM-CpPhtBu), and phenyl (DIM-C-pPhC 6 H 5 ) substituents have been identified as a new class of peroxisome proliferator-activated receptor ; (PPAR;) agonists that exhibit antitumorigenic activity. The PPAR;-active C-DIMs have not previously been studied against bladder cancer. We investigated the effects of the PPAR;-active C-DIMs on bladder cancer cells in vitro and bladder tumors in vivo. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
90
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 91 publications
(97 citation statements)
references
References 34 publications
7
90
0
Order By: Relevance
“…1C. The higher growth inhibitory activity of DIM-C-pPhtBu and related compounds compared with thiazolidinediones has also been observed in bladder, colon, and pancreatic cancer cells (37,38,41).…”
Section: Discussionmentioning
confidence: 94%
“…1C. The higher growth inhibitory activity of DIM-C-pPhtBu and related compounds compared with thiazolidinediones has also been observed in bladder, colon, and pancreatic cancer cells (37,38,41).…”
Section: Discussionmentioning
confidence: 94%
“…How curcumin overcomes resistance to IFN-a is unclear, but a previous study showed that this cytokine mediates its apoptotic effects through the induction of TRAIL (34). Similar to curcumin, genistein (derived from soy) and analogues of indole-3-carbinol (derived from cruciferous vegetables) have been shown to suppress the proliferation of bladder cancer cells (35,36). Curcumin has been shown to have no effect on normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Whether all of these effects of curcumin are mediated by targeting NF-nB is not clear. Previously, we showed that the indole-3-carbinol analogue DIM can mediate its effects against bladder cancer by targeting peroxisome proliferator-activated receptor-g (36). Curcumin is agonist of peroxisome proliferator-activated receptor-g as well (41).…”
Section: Discussionmentioning
confidence: 99%
“…18 To silence endogenous Nurr1, we used small interfering RNA-oligo targeting Nurr1 purchased from Ambion (Austin, Tex); sense: 5 0 -GGCUUGUAAAUUUACCCAA TT-3 0 , antisense: 5 0 -UUGGGUAAAUUUACAAGCC TT-3 0 . As nontargeting control, Silencer Negative Control small interfering RNA (Ambion) was used.…”
Section: Immunohistochemical Analysismentioning
confidence: 99%
“…Thereafter, for cell viability, 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay was performed as described previously. 18 For migration assay, a modified Boyden Chamber method was used. 19 In brief, 2.5 Â 10 4 cells in 500 lL were seeded into the transwell insert chamber with a filter, and the inserts were placed in the lower chambers filled with 750 lL of RPMI-1640 containing 5% fetal calf serum.…”
Section: Immunohistochemical Analysismentioning
confidence: 99%